Small-molecule PROTAC degraders of the Bromodomain and Extra Terminal (BET) proteins — A review. (April 2019) - Yang, Chao-Yie; Qin, Chong; Bai, Longchuan; Wang, Shaomeng
Abstract : ThePRO teolysisTA rgetingC himeric (PROTAC) concept has provided an opportunity for the discovery and development of a completely new type of therapy involving induction of protein degradation. The BET proteins, comprised of BRD2, BRD3, BRD4 and the testis-specific BRDT protein, are epigenetic readers and master transcription coactivators. Extremely potent and efficacious small-molecule PROTAC degraders of the BET proteins, based on available, potent and selective BET inhibitors, have been reported. BET degraders differ from BET inhibitors in their cellular potency, phenotypic effects, pharmacokinetic properties and toxicity profiles. Herein, we provide a review of BET degraders and the differential outcome observed in the cellular and animal models for BET degraders in comparison to BET inhibitors.